STRATEGI PROMOSI DI MEDIA SOSIAL INSTAGRAM TERHADAP KESADARAN MEREK DI ERA GENERASI Z - Lailatus Sa’diya (Universitas Trunojoyo Madura, 2017)
Along with technological developments, the people of today's digital world. Where gadgets and the Internet is a basic requirement of the community that we are familiar with the term generation Z. Generation Z is the generation of all-round internet connection wherever and whenever. They spend more time on various social, economic, political, and lifestyle activities. The existence of social media Instagram into the arena of existence and looking for various ways in determining shopping options. This research uses qualitative method with phenomenology approach. The results of this study found Generation Z Instagram users will easily see a product that is promoted through Instagram in the form of photos or video and remember the product. anytime viewed on the Instagram homepage. The more often seen it will often they remember the product until finally reaching the brand awareness.